St. Lucia : Staff Report for the 2010 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2010)
This 2010 Article IV Consultation highlights that macroeconomic outcomes have weakened significantly for St. Lucia. Real GDP is estimated to have contracted by 5.2 percent in 2009, reflecting a sharp decline in visitor arrivals and construction activity related to foreign direct investment. For 2010, the outlook is for a nascent recovery, supported by higher advance hotel bookings and additional flights to the island. Against this backdrop, Executive Directors have welcomed the authorities' commitment to implement a credible fiscal framework to achieve fiscal sustainability.